La propaganda exterior de la República durante la Guerra Civil - Hugo García (Mélanges de la Casa de Velázquez, 2009)
This article seeks to examine the international impact of the Civil War in more depth through an analysis of the Republican propaganda campaign in France during the war. It examines the creation, organization and functioning of the principal services set up by the loyal Government in Paris, a parallel centre for the exterior projection of the Republican State following the opening of the Offices of the Under-Secretariat for Propaganda in July 1937. The paper shows how the Government campaign in France, as in other countries, was hampered by the conflicts of demarcation between diplomatic and propaganda chiefs and the tendency of the authorities to look for alternative channels (such as the Communist International) through which to defend their positions. These problems, added to the shortage of funds during the latter stages of the war, may account for the lack of coherence in the Republican campaign and its apparently poor results.